Exploring the Influence of Artificial Intelligence (AI) on Islamic Thinking Among Students at Universitas Zainul Hasan Genggong Probolinggo - Arifin , Nur Musrifah; Ainol; Herwati (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2025)
The increasing application of artificial intelligence (AI) in academic activities, including the study of Islamic materials, raises important questions about its impact on students' Islamic thinking. This study aims to determine the extent to which AI influences Islamic thinking among students of the Islamic Education Study Program at Universitas Islam Zainul Hasan Genggong. This study involved 83 students from the 2021 cohort. Data were collected through a closed-ended questionnaire and analyzed using partial least squares structural equation modeling (PLS-SEM) via the SmartPLS application. The results indicate that the use of AI positively and significantly influences students' Islamic thinking, as evidenced by a path coefficient of 0.810, a t-value of 20.654, and a p-value of 0.000. The R-square value of 0.656 indicates a moderate contribution of AI to Islamic thinking, while the F-square value of 1.905 reflects a strong influence. These findings can serve as a reference for educators in developing learning strategies that maintain a critical approach to Islamic studies amid the widespread use of AI. Additionally, this study is expected to enhance students' awareness of using AI as an academic tool while acknowledging the importance of primary Islamic sources in understanding Islamic teachings.